DIGITAL MARKETING STRATEGY, BRANDING IN INCREASING TRUST AND SALES AT PT AGRODANA FUTURES - Arrum Mawarni; Bowo Santoso (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to explore in depth the implementation of digital marketing and branding strategiesin building trust and increasing sales within financial service companies, particularly at PT Agrodana Futures. The research was conducted using an internship based practical method over a four month period, during which the researcher was directly involved in the planning, execution, and evaluation of the company's marketing activities, especially those based on digital platforms. Observation indicates that PT Agrodana Futures employs digital marketing strategies by using social media platforms (Instagram and YouTube) its official website, and regularly held educational. webinars to deliver market information, investment education, and to strengthen its image as a legal and professional company. The branding strategy is reinforced through consistent visual identity and emphasis on the official regulations that oversee the company, such as BAPPEBTI and the Jakarta Futures Exchange. The success of this strategy is reflected in increased participation in digital activities, greater public trust as evidenced by feedback and digital interaction and a rise in the number of new customer accounts during the internship period. This study concludes that the synergy between education based digital marketing strategies and credibility oriented branding has a significant impact on customer perceptions and decision making. This research provides practical contributions for financial service companies seeking to build trust amidst competition and the dynamics of the digital industry.